ANALYSIS OF THE RETIREMENT PREPARATION PROGRAM OF THE FEDERAL UNIVERSITY OF ESPÍRITO SANTO: A STUDY ON ITS IMPACTS AND EFFICACY (REMUNOM, 2025)
This article investigated the perception of employees of the Federal University of Espírito Santo (UFES) about the Retirement Preparation Program (PPA), implemented between 2017 and 2021, in three dimensions: health and autonomy, occupation and post-career, and social support. The survey method was used with convenience sampling, whose data were collected through semi-structured interviews and analyzed through content analysis. The results indicated that a) there is a lack of financial planning for retirement, b) encouragement to practice healthy habits, c) preparation for post-career occupation was praised, and d) the respondents value the social support network. The conclusion shows that the retirement program studied is considered essential and relevant as a people's well-being policy for the participants. The main contribution of this study to science is the confirmation that retirement programs based on psychosocial principles and well-being allow a reduction in negative aspects of this period, such as depression, anxiety, and isolation.